FUNDAMENTAL PARAMETERS AND CHEMICAL COMPOSITION OF CEPHEID X SGR. - Usenko, I. A.; Knyazev, A. Yu.; Berdnikov, L. N.; Kravtsov, V. V. (Одеські астрономічні публікації, 2012)
Five high-resolutioned spectra of unusual Cepheid X Sgr have been obtained during its pulsational period. For the first time we obtain accurate fundamental parameters and abundances of chemical elements, in particular of sodium, magnesium and aluminium. We estimate the mean Teff = 6143±30 K; log g = 2.00; Vt = 4.35 kms -1. The estimated effective temperature and surface gravity are relatively high compared to the typical values characteristic of Cepheids with pulsational period around 7 days. A deficit of carbon ([C/H] = -0.26±0.04 dex), overabundances of sodium ([Na/H] =+0.31±0.04 dex) and aluminium ([Al/H] = +0.21±0.08 dex) are typical for Cepheids passing through the first dredge-up phase. However, an obvious overabundance of magnesium ([Mg/H] = +0.19±0.04 dex) is unusual. The abundance of iron ([Fe/H] = -0.02±0.01 dex) is very close to the solar one. Abundances of a - elements, (those of Fe-group, as well as "light " and "heavy", s- and r-process elements) are comparable to the solar values, except for several elements showing slight over- or underabundances.